Decolonial Shift or Coloniality? Regional Cooperation in East and Southeast Asia - Zhang, You (International Higher Education, 2025)
<h3 id="calls-to-decolonize-global-higher-education-are-growing-in-east-and-southeast-asia-increasing-regional-cooperation-reflects-a-decolonial-shift-challenging-western-dominance-in-global-higher-education-however-regional-cooperation-is-often-regarded-as-secondary-to-partnerships-with-western-institutions-raising-concerns-that-actors-in-the-region-may-inadvertently-perpetuate-western-hegemony-in-global-higher-education" data-pm-slice="1 1 []">Calls to decolonize global higher education are growing. In East and Southeast Asia, increasing regional cooperation reflects a decolonial shift, challenging Western dominance in global higher education. However, regional cooperation is often regarded as secondary to partnerships with Western institutions, raising concerns that actors in the region may inadvertently perpetuate Western hegemony in global higher education.